MAGISTERIUM AS THE ENEMY OF LIBERAL THOUGHTS IN PHILLIP PULLMAN’S NORTHERN LIGHTS - Nabil Bakri (Rubikon : Journal of Transnational American Studies, 2019)
Pullman’s Northern Lights is considered by many as a representation of negative criticism toward religion, especially Christianity, for its depictions of the Magisterium. Many researches aim to unravel Pullman’s criticism and prove whether or not the novel is about ‘killing God’, resulting in the general perception that Northern Lights is a condemnation of religion.  By comparing the novel to the history of Medieval Church and the power of Magisterium to the Bible, this analysis means to prove whether or not the criticism is addressed to religion and to figure out who really ‘kills God’ that becomes the essential point of Pullman’s criticism in the novel. Using Marxism and its relation to power abuse, this analysis attempts to relate Pullman’s Magisterium to the real Magisterium and how the institution gains its power from God as mentioned in the holy Bible. Magisterium in Northern Lights does not represent God’s will. It serves instead as a critic of who kills God and therefore, it is not a form of literature to condemn religion.Keywords: magisterium; medieval church; scripture; fantasy; power abuse